Comparison of the effects of umbilical cord cryoextract and lyophilized form on the adhesive, proliferative, and metabolic properties of various cell types - Kaverinska, A.; Prokopiuk, V.Yu. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2024)
The objective was to ascertain the potential of cryo-umbilical cord extract as an alternative to fetal bovine serum (FBS), which is conventionally employed to stimulate cell growth but is subject to ethical and safety constraints. The umbilical cord cryo-extract is a rich source of bioactive components that have been demonstrated to enhance the adhesive, proliferative and metabolic activity of cells. Furthermore, it has been shown to be an effective substitute for serum in the cultivation of various cell types, making it a promising candidate for use in cellular technology and regenerative medicine. The findings of the experimental study demonstrated that the cryoextract of the umbilical cord exhibited a notable enhancement in the adhesive and proliferative attributes of the cells, when compared to the other conditions that were investigated. The fibroblasts demonstrated high adhesion and rapid migration in the presence of the cryoextract, which provides advantages for potential use in the restoration of the connective tissue stroma of various organs and skin. The nerve cells demonstrated enhanced viability and stability in comparison to FBS, which renders the umbilical cord cryoextract a promising candidate for incorporation into neuroregenerative technologies. Furthermore, the cryoextract exhibited a substantial beneficial impact on fetal liver cells, augmenting their metabolic activity and adhesion, thereby opening avenues for investigation into liver regeneration. The effect on splenocytes was also favorable, indicating that it can be employed to bolster immune function in circumstances where immune response regulation is necessary. The lyophilized cryoextract demonstrated a limited positive effect, particularly in relation to its adhesive and proliferative properties. However, this effect was less pronounced than that observed in the cryoextract. The addition of the lyophilized cryoextract to nerve cells and fibroblasts resulted in a reduction in adhesion and migration activity, indicating the necessity for optimization of the lyophilization process to preserve the biological activity of the extract. However, the stability of the lyophilized cryoextract and its capacity for long-term storage render it a valuable resource in situations where the preservation of bioactive components and a prolonged shelf life are of significance. Thus, cord cryoextract represents a promising alternative to FBS, which has the potential to provide the necessary support for cell growth, adhesion and proliferation. Nevertheless, the technology employed in the production of cryo-umbilical cord extract lyophilizate must undergo further refinement in order to attain the same efficacy as that observed in cryoextract. Further research should concentrate on a comprehensive examination of the mechanisms of action of cryoextract, in addition to the optimization of lyophilization techniques to adapt this product to the requirements of cell technology and regenerative medicine. This will facilitate its wider application in the stimulation of tissue regeneration and the restoration of functional activity in various organs.